Determinants of asthma phenotypes in supermarket bakery workers - Baatjies, R; Lopata, A L; Sander, I; Raulf-Heimsoth, M; Bateman, E D; Meijster, T; Heederik, D; Robins, T G; Jeebhay, M F (The European respiratory journal, 2009)
While baker's asthma has been well described, various asthma phenotypes in bakery workers have yet to be characterised. Our study aims to describe the asthma phenotypes in supermarket bakery workers in relation to host risk factors and self-reported exposure to flour dust. A cross-sectional study of 517 supermarket bakery workers in 31 bakeries used a questionnaire, skin prick tests, and specific immunoglobulin E to wheat, rye and fungal alpha-amylase and methacholine challenge testing. The prevalence of probable occupational asthma (OA, 13%) was higher than atopic (6%), nonatopic (6%) and work-aggravated asthma (WAA, 3%) phenotypes. Previous episodes of high exposure to dusts, fumes and vapours causing asthma symptoms were more strongly associated with WAA (OR 5.8, 95% CI 1.7-19.2) than OA (2.8, 1.4-5.5). Work-related ocular-nasal symptoms were significantly associated with WAA (4.3, 1.3-13.8) and OA (3.1, 1.8-5.5). Bakers with OA had an increased odds ratio of reporting adverse reactions to ingested grain products (6.4, 2.0-19.8). OA is the most common phenotype among supermarket bakery workers. Analysis of risk factors contributes to defining clinical phenotypes, which will guide ongoing medical surveillance and clinical management of bakery workers.